Perbedaan Sensitivitas Spesifisitas Skor Apfel Dan Skor Koivuranta Sebagai Prediktor Kejadian PONV Dengan Anestesi Umum - Anna Millizia; Teuku Yudhi Iqbal; Putra Futtaqi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Post Operative Nausea and Vomiting (PONV) is a state of nausea and vomiting that occurs during the first 24 hours after surgery. The Apfel score and Koivuranta score are predictor scores used to predict PONV, currently there is no research that shows which score is more accurate in predicting PONV at RSU Cut Meutia Aceh Utara and to reduce the time of anamnese it is necessary to obtain one of the scores which has the higher accuracy between the two scores. This study aims to determine the difference between Apfel scores and Koivuranta scores as predictors of PONV at RSU Cut Meutia Aceh Utara and to find out which scores are more accurate in predicting PONV. This research is an analytic observational study through a cross sectional approach. The analysis in this study uses a diagnostic test. Sampling in this study used the accidental sampling method, as many as 54 patients who met the inclusion and exclusion requirements. The results of the diagnostic test, the sensitivity and specificity of the Apfel score were 84.6% and 78.0% with an ROC value of 0.829. The Koivuranta score has a sensitivity and specificity value of 76.9% and 78.0% with an ROC value of 0.811. The Apfel score is more accurate and has a simpler scoring variable than the Koivuranta score in predicting PONV.